Genome-wide association study identifying variants related to performance and injury in high-performance athletes - Ebert, J. R.; Magi, A.; Unt, E.; Prans, E.; Wood, D. J.; Koks, S. (Experimental Biology and Medicine, 2023)
A growing body of evidence exists supporting the role that genetic variation plays in athletic performance and injury. This study sought to identify genetic variants associated with performance and lower limb musculoskeletal injury in a high-level athletic cohort. A total of 126 Estonian National Team members (Olympic athletes and participants of International Championships) (104 males, 82.5%) underwent a genome-wide association analysis between 2017 and 2018, to identify single-nucleotide polymorphisms (SNPs) associated with performance and/or injury. The athletic cohort was stratified within each sport based on performance and whether they were a medalist (n = 29) or not (n = 97), whether they sustained an injury (n = 47) or not (n = 79), and the type of injury (patella tendinopathy n = 22, Achilles tendinopathy n = 17, hamstring injury n = 3, anterior cruciate ligament rupture n = 6). Three SNPs demonstrated strong genome-wide association with athletic performance (podium/medalist versus not), including DSG1 (rs10502567, OR 14.3) and DSG4 (rs73410248, OR 17.4), while 76 SNPs demonstrated suggestive significance. Overall, 37 SNPs gave genome-wide suggestive association with any type of injury, including PAPPA2 (rs11580456, OR 13.8) and MAS1 (rs220735, rs170219, OR 3.1) which demonstrated positive signal with multiple SNPs. Several genes demonstrated positive association for the specific injury types, including COL22A1 (rs3924862) and PLXNA2 (rs11799530), as well as PAPPA2 (rs11580456), DOK5 (rs73142922), GNG12 (rs28435277), and DAP (rs267959, rs2930047, rs1080440, rs267939). The current study identified genetic variants associated with high-level athletic performance and musculoskeletal injury. Further work is required to permit integration of this and future knowledge into individualized training practices, as well as injury mitigation and rehabilitation programs.